The cognitive impacts of Chinese pinyin learning on English-speaking elementary students in a bilingual educational setting - Liu, Jingzhi; Bai, Hao (Frontiers in Psychology, 2025)
This study investigates the effects of limited Chinese pinyin learning on American elementary school students' language performance, with particular emphasis on potential cross-linguistic interference and the benefits of pinyin learning. Participants from two schools, one receiving Chinese instruction including pinyin (experimental group) and one with no Chinese instruction (control group), in first and fourth grades were assessed on measures of Nonverbal Ability (NA), Phonological Awareness (PA), the Peabody Picture Vocabulary Test (PPVT-4), Chinese Fluency Test (CFT), Commonly Mispronounced Chinese Words Read Aloud Test (CMCT), and Commonly Mispronounced English Words Read Aloud Test (CMET). Results indicated that the modest exposure to pinyin, delivered as five 30-min sessions per three weeks, did not significantly interfere with the acquisition of English vocabulary, as evidenced by comparable performance on PPVT-4 and CMET across groups. In first grade, CMCT was positively correlated with NA, PA, and CMET, while in fourth grade, significant correlations were observed only with CMET and CFT. Furthermore, error analyses revealed that the majority of mis- pronunciations were attributable to intrinsic properties of the English language rather than to negative transfer from pinyin instruction. These differential patterns suggest that a developmental shift in how Chinese pinyin interacts with students' cognitive and linguistic abilities across grade levels, the most effective period for introducing pinyin instruction appears to be around the first grade, when phonological systems are still developing, while by fourth grade, when these systems are largely consolidated, the cognitive benefits of pinyin learning become less direct, although early pinyin skills then appear to support vocabulary acquisition.